Analisis Kemampuan Siswa Dalam Menyelesaikan Soal Cerita Pokok Bahasan Program Linear - Herlina Ahmad; Nurhidayah Nurhidayah; Nurdin Nurdin (Universitas Muslim Nusantara Al Washliyah, 2018)
Abstract The main problem in this study is the number of students who feel overwhelmed in solving math problems, especially in the form of story problems on the subject linear program. So this study aims to determine the students' traits in solving the story problem on the subject of linear programming, through research